Data for "The impact of surface polarisation on the degradation of tunnel oxide passivating contacts in silicon solar cells" - Liu, D; Wright, M; Altermatt, P; Wright, B; Hamer, P; Bonilla, RS (University of Oxford, 2024)
Tabulated data sets associated with publication, in MS Excel.